2020
DOI: 10.1111/nmo.13837
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorating effects of sacral neuromodulation on gastric and small intestinal dysmotility mediated via a sacral afferent‐vagal efferent pathway

Abstract: Background/AimsIn a recent study of sacral nerve stimulation (SNS) for colonic inflammation, a possible spinal‐vagal pathway was implicated. The aim of this study was to provide evidence for such a pathway by investigating the effects of SNS on dysmotility of the stomach and duodenum that are not directly innervated by the sacral efferents.MethodsTwenty‐seven rats were chronically implanted with wire electrodes for SNS and gastrointestinal slow waves. SNS was performed in several acute sessions to investigate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 49 publications
1
11
0
Order By: Relevance
“…Moreover, we found that aVNS also improved the impairments induced by loperamide in both gastric and intestinal slow waves. The impairments and changes in GI slow waves were comparable to that of FD rats and diabetic rats with delayed gastric emptying and dysrhythmia (decreased normal slow waves) 30,31 . Recently, Sukasem et al 56 reported that transcutaneous aVNS also effectively altered the frequency and amplitude of gastric slow waves in healthy pigs.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Moreover, we found that aVNS also improved the impairments induced by loperamide in both gastric and intestinal slow waves. The impairments and changes in GI slow waves were comparable to that of FD rats and diabetic rats with delayed gastric emptying and dysrhythmia (decreased normal slow waves) 30,31 . Recently, Sukasem et al 56 reported that transcutaneous aVNS also effectively altered the frequency and amplitude of gastric slow waves in healthy pigs.…”
Section: Discussionmentioning
confidence: 87%
“…aVNS was performed using parameters of 25 Hz, 0.5 ms, 2 s on, 3 s off and amplitude of 90% motor threshold (range from 1 to 2 mA). The motor threshold was defined as the minimum amplitude of stimulation at which the animal's ear began to shake, and the motor threshold was determined at the beginning of each experiment 29,30 . Animals received aVNS at the conchae of the right ear for 1 h daily for 7 days (from D7 to D14).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We speculated that this might be attributed to (a) possible innervation of the vagus nerve to the rectum and/or (b) a possible vagal afferent and sacral efferent pathway. In a few recent studies, sacral nerve stimulation was reported to alter functions of the gastrointestinal organs (stomach and small intestine) that are not innervated with the sacral nerve ( 77 , 78 ), and a spinal afferent and vagal efferent pathway was indicated with the sacral nerve stimulation ( 79 ).…”
Section: Discussionmentioning
confidence: 99%
“…aVNS was performed using parameters of 25 Hz, 0.5 msec, 2 sec on, 3 sec off, and amplitude of 90% motor threshold (range from 1 to 2 mA). The motor threshold was defined as the minimum amplitude of stimulation at which the animal's ear began to shake (29,30). Animals received aVNS unilaterally (right ear) in both acute and chronic study, but with different stimulation duration.…”
Section: Auricular Vagal Nerve Stimulationmentioning
confidence: 99%